Money politic as the bribery in the Election for Regional Head in Indonesia - Herman, Herman (Technium Social Sciences Journal, 2022)
Money politic in election for regional head in Indonesia is the behavior of group of people who destroy democracy. Money politic in the general election in Indonesia have become commonplace. The purpose of this research is to analyze money politic in election for regional head in Indonesia. The research method used is the normative legal research method, with the analysis approach to the Law of the election for regional head in Indonesia. The result of research showed that money politic in election for regional head in Indonesia, Based on the Law of 10 of 2016, money politic constitutes bribery. The category of bribery due to money politic contains the tendency of giving money to influence voters to choose or not for candidate.